Preparation method of high-strength rare earth magnesium-based composite material and product
Patent Information
- Application Number
- CN202410596388.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-14
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-05-14
AI Technical Summary
The absolute strength and stiffness of existing titanium particle reinforced magnesium matrix composites are still relatively low, and the precipitation behavior of aged precipitates is limited by existing technologies, which are specific problems that existing technologies cannot effectively solve.
The bar stock is prepared by differential temperature hot extrusion deformation process: Mg-Gd-Y-Zr alloy is melted at 720℃. After the alloy is completely melted, the furnace temperature is reduced to 625-640℃ and held for 5-10 minutes. When the melt is semi-solid, TA1 titanium alloy spherical powder is added. The mixture is stirred at 400-600 rpm for 30 minutes and then cast into an ingot.
By using a rotary forging process, the matrix is made into a deformed structure with high strain. At the same time, the spherical TA1 titanium alloy particles introduced can create a higher local stress pile-up around the particles. The combination of the two can significantly increase the number of crystal defects such as stacking faults and dislocations in the rare earth magnesium matrix composite matrix. During the later aging process, it can provide more nucleation sites for the aging precipitates, promote the precipitation behavior during the aging process, and thus obtain the strengthening precipitates with smaller size and denser distribution, so that the final rare earth magnesium matrix composite material has higher strength.
Smart Images

Figure CN118497577B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of magnesium alloy materials technology, and relates to a method for preparing high-strength rare earth magnesium-based composite materials and products. Background Technology
[0002] Adding heterogeneous particles to magnesium alloys to enhance their absolute strength and stiffness provides a new approach to overcoming the technical bottleneck of low absolute strength and stiffness in magnesium alloys. Currently, titanium particles are often used as a reinforcing phase to improve the absolute strength and stiffness of magnesium-based composites. However, compared with metal structural materials such as steel and aluminum alloys, the absolute strength and stiffness of existing titanium particle-reinforced magnesium-based composites remain relatively low. To further improve the strength of magnesium-based composites, the preparation of high-strength or even ultra-high-strength magnesium-based composites remains an important research topic in the field of composite materials.
[0003] For age-hardening materials, crystal defects such as stacking faults and dislocations can provide more nucleation sites for age-hardening precipitates, promoting precipitation behavior during the aging process and resulting in smaller and more densely distributed strengthening precipitates. However, due to the inherent plastic deformation capacity of the alloy material, obtaining even higher densities of crystallographic defects is a significant challenge, thus hindering the precipitation of strengthening precipitates during aging and impeding further improvements in alloy strength.
[0004] Currently, most researchers rely on adding heterogeneous reinforcing particles or using a single strain-aging strengthening method on age-hardened magnesium alloys. However, due to the limited variety of preparation methods, the performance improvement of the materials is limited. Summary of the Invention
[0005] In view of this, one objective of the present invention is to provide a method for preparing a high-strength rare earth magnesium-based composite material; the other objective is to provide a high-strength rare earth magnesium-based composite material.
[0006] To achieve the above objectives, the present invention provides the following technical solution:
[0007] 1. A method for preparing a high-strength rare-earth magnesium-based composite material, the method being as follows:
[0008] S1. By mass percentage: 3-10 wt.% of TA1 titanium alloy spherical powder, with the balance being Mg-Gd-Y-Zr alloy;
[0009] S2, Manufacturing ingots;
[0010] S3. Homogenize the ingots obtained in S2;
[0011] S4. The ingots treated by S3 are extruded and deformed to obtain bars.
[0012] S5. Perform rotary forging deformation on the bar obtained in S4.
[0013] S6. Aging treatment is then performed on the bars that have been treated in S5.
[0014] Preferably, in step S2, a semi-solid stirring casting process is used to prepare the ingot, specifically as follows:
[0015] The Mg-Gd-Y-Zr alloy is melted at 720℃. After the alloy is completely melted, the furnace temperature is lowered to 625-640℃ and held for 5-10 minutes. When the melt is semi-solid, TA1 titanium alloy spherical powder is added. The mixture is stirred at 400-600 rpm for 30-40 minutes. The furnace temperature is then raised to 680-700℃ and stirred at 400-600 rpm for 20-30 minutes. The mixture is then cast into an ingot.
[0016] Preferably, in step S3, the homogenization treatment specifically involves: dissolving the ingot obtained in step S2 at 480–520°C for 8–12 hours.
[0017] Preferably, in step S4, the bar stock is prepared using a differential temperature hot extrusion deformation process. Specifically, the ingot treated in S3 is preheated to 450–500°C, the extrusion die is preheated to 400–450°C, and then forward extrusion is performed at an extrusion ratio of 25:1. During the extrusion deformation process, the temperature of the ingot is higher than that of the extrusion die. The higher ingot temperature can improve the fluidity of the composite material during deformation, thereby improving the formability of the composite material and preventing extrusion defects such as surface cracking. Secondly, the higher ingot temperature can prevent supersaturated solute atoms from precipitating during deformation, thus helping to improve the age-strengthening effect of the composite material. In addition, the temperature difference between the ingot and the die can suppress the abnormal growth of dynamically recrystallized grains during extrusion, thereby obtaining a fully recrystallized extruded bar stock with fine grains.
[0018] Preferably, in step S5, the rotary forging deformation process specifically involves controlling the deformation amount per pass to be 2% to 10%, the total deformation amount to be 20% to 45%, and reversing the feeding direction after each rotary forging process.
[0019] Preferably, in step S6, the aging treatment specifically involves aging the bar material treated in S5 at 200°C for 40–50 hours.
[0020] Preferably, in step S1, the average particle size of the TA1 titanium alloy spherical powder is 10 μm.
[0021] Preferably, in step S1, the Mg-Gd-Y-Zr alloy is composed of the following components by mass percentage: 8-10 wt.% Gd, 2-4 wt.% Y, 0.1-0.5 wt.% Zr, unavoidable impurities ≤0.25 wt.%, and the balance being Mg.
[0022] 2. High-strength rare earth magnesium-based composite material prepared by the method described above.
[0023] The beneficial effects of this invention are as follows: This invention provides a method for preparing high-strength rare-earth magnesium-based composite materials and a product. During the preparation of this material, a rotary forging deformation process is used to obtain a high-strain deformed microstructure in the matrix. Simultaneously, the introduction of TA1 titanium alloy spherical particles can create higher local stress pile-up around the particles. The combination of these two factors significantly increases the number of stacking faults, dislocations, and other crystal defects in the rare-earth magnesium-based composite material matrix. During subsequent aging, this provides more nucleation sites for aging precipitates, promoting precipitation behavior during the aging process, thereby obtaining smaller and more densely distributed strengthening precipitates, resulting in a rare-earth magnesium-based composite material with higher strength. This method is simple, easy to operate, low-cost, and more economical and scalable.
[0024] Other advantages, objectives, and features of the invention will be set forth in part in the description which follows, and in part will be apparent to those skilled in the art from the following examination, or may be learned from practice of the invention. The objectives and other advantages of the invention can be realized and obtained through the following description. Attached Figure Description
[0025] To make the objectives, technical solutions, and advantages of the present invention clearer, the preferred embodiments of the present invention will be described in detail below with reference to the accompanying drawings, wherein:
[0026] Figure 1 Metallographic images of the rods prepared in step S4 of Examples 1, 2, and Comparative Example 1 are shown. Figure 1 In Figure a, the metallographic image of the rod prepared in step S4 of Comparative Example 1 is shown. Figure 1 In Figure b, the metallographic image of the rod prepared in step S4 of Example 1 is shown. Figure 1 c is a metallographic image of the rod prepared in step S4 of Example 2;
[0027] Figure 2 The images show the EBSD values of the bars after rotary forging deformation treatment in step S5 of Example 1 and Comparative Example 1 at 500x magnification. Figure 2 In Figure a, the bar after rotary forging deformation treatment in step S5 of Example 1 is viewed at 500x magnification using the EBSD method. Figure 2 In Figure b, the bar after rotary forging deformation in step S5 of Comparative Example 1 is plotted at 500x magnification using the EBSD method.
[0028] Figure 3 The images show the KAM diagrams of the bars after rotary forging deformation treatment in step S5 of Example 1 and Comparative Example 1 at 500x magnification. Figure 3 In Figure a, the bar after rotary forging deformation treatment in step S5 of Example 1 is plotted at 500x KAM. Figure 3 In Figure b, the KAM image of the bar after rotary forging deformation in step S5 of Comparative Example 1 is magnified at 500x.
[0029] Figure 4 This is a transmission microscope image of grains with large local orientation differences in the bar obtained by rotary forging deformation treatment in step S5 of Example 1. Detailed Implementation
[0030] The following specific examples illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and various details in this specification can also be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention.
[0031] Example 1
[0032] Preparation of high-strength rare earth magnesium-based composite materials
[0033] S1. By mass percentage: 3 wt.% of TA1 titanium alloy spherical powder with an average particle size of 10 μm, with the balance being Mg-Gd-Y-Zr alloy. This Mg-Gd-Y-Zr alloy, by mass percentage, consists of the following components: 9 wt.% Gd, 3 wt.% Y, 0.5 wt.% Zr, unavoidable impurities ≤0.25 wt.%, with the balance being Mg.
[0034] S2. Ingot preparation using semi-solid stirring casting process: Mg-Gd-Y-Zr alloy is melted at 720℃. After the alloy is completely melted, the furnace temperature is lowered to 635℃ and held for 5 minutes. When the melt is semi-solid, TA1 titanium alloy spherical powder is added. The mixture is stirred at 600 rpm for 30 minutes. The furnace temperature is then raised to 680℃ and stirred at 600 rpm for 20 minutes. The ingot is then cast.
[0035] S3. Homogenization treatment: The ingot obtained in step S2 is solution treated at 500℃ for 10 hours;
[0036] S4. Bar stock is prepared by differential temperature hot extrusion deformation process: the ingot treated by S3 is preheated to 500°C, the extrusion die is preheated to 415°C, and then forward extrusion is carried out under the condition of extrusion ratio of 25:1.
[0037] S5. Rotary forging deformation treatment: The bar obtained in S4 is subjected to rotary forging deformation treatment. The deformation amount per pass is controlled at 3%, and the total deformation amount is 23%. After each rotary forging treatment, the feeding direction is reversed to obtain a bar with a diameter of 14.5mm.
[0038] S6. Aging treatment: The bar material treated with S5 is aged at 200℃ for 49 hours.
[0039] Example 2
[0040] Preparation of high-strength rare earth magnesium-based composite materials
[0041] The difference from Example 1 is that in step S1, the ingredients are prepared by mass percentage: 6 wt.% of TA1 titanium alloy spherical powder with an average particle size of 10 μm, and the balance is Mg-Gd-Y-Zr alloy.
[0042] Example 3
[0043] Preparation of high-strength rare earth magnesium-based composite materials
[0044] S1. By mass percentage: 3 wt.% of TA1 titanium alloy spherical powder with an average particle size of 10 μm, with the balance being Mg-Gd-Y-Zr alloy. This Mg-Gd-Y-Zr alloy, by mass percentage, consists of the following components: 8 wt.% Gd, 4 wt.% Y, 0.1 wt.% Zr, unavoidable impurities ≤0.25 wt.%, with the balance being Mg.
[0045] S2. Ingot preparation using semi-solid stirring casting process: Mg-Gd-Y-Zr alloy is melted at 720℃. After the alloy is completely melted, the furnace temperature is lowered to 625℃ and held for 10 minutes. When the melt is semi-solid, TA1 titanium alloy spherical powder is added. The mixture is stirred at 500 rpm for 35 minutes. The furnace temperature is then raised to 680℃ and stirred at 500 rpm for 25 minutes. The ingot is then cast.
[0046] S3. Homogenization treatment: The ingot obtained in step S2 is solution treated at 520℃ for 8 hours;
[0047] S4. Bar stock is prepared by differential temperature hot extrusion deformation process: the ingot treated by S3 is preheated to 450°C, the extrusion die is preheated to 400°C, and then forward extrusion is carried out under the condition of extrusion ratio of 25:1.
[0048] S5. Rotary forging deformation treatment: The bar obtained in S4 is subjected to rotary forging deformation treatment. The deformation amount per pass is controlled at 6%, and the total deformation amount is 45%. After each rotary forging treatment, the feeding direction is reversed to obtain a bar with a diameter of 12.5mm.
[0049] S6. Aging treatment: The bar material treated with S5 is aged at 200℃ for 40 hours.
[0050] Example 4
[0051] Preparation of high-strength rare earth magnesium-based composite materials
[0052] S1. By mass percentage: 6 wt.% of TA1 titanium alloy spherical powder with an average particle size of 10 μm, with the balance being Mg-Gd-Y-Zr alloy. This Mg-Gd-Y-Zr alloy, by mass percentage, consists of the following components: 10 wt.% Gd, 2 wt.% Y, 0.3 wt.% Zr, unavoidable impurities ≤0.25 wt.%, with the balance being Mg.
[0053] S2. Ingot preparation using semi-solid stirring casting process: Mg-Gd-Y-Zr alloy is melted at 720℃. After the alloy is completely melted, the furnace temperature is lowered to 640℃ and held for 7 minutes. When the melt is semi-solid, TA1 titanium alloy spherical powder is added. The mixture is stirred at 400 rpm for 40 minutes. The furnace temperature is then raised to 700℃ and stirred at 400 rpm for another 30 minutes. The ingot is then cast.
[0054] S3. Homogenization treatment: The ingot obtained in step S2 is solution treated at 480℃ for 12 hours;
[0055] S4. Bar stock is prepared by differential temperature hot extrusion deformation process: the ingot treated by S3 is preheated to 480°C, the extrusion die is preheated to 450°C, and then forward extrusion is carried out under the condition of extrusion ratio of 25:1.
[0056] S5. Rotary forging deformation treatment: The bar obtained in S4 is subjected to rotary forging deformation treatment. The deformation amount per pass is controlled at 6%, and the total deformation amount is 45%. After each rotary forging treatment, the feeding direction is reversed to obtain a bar with a diameter of 12.5mm.
[0057] S6. Aging treatment: The bar material treated with S5 is aged at 200℃ for 40 hours.
[0058] Comparative Example 1
[0059] Preparation of rare earth magnesium-based composite materials
[0060] The difference from Example 1 is that, in step S1, TA1 titanium alloy spherical powder with an average particle size of 10 μm was not added.
[0061] Comparative Example 2
[0062] Preparation of rare earth magnesium-based composite materials
[0063] The difference from Example 1 is that no rotary forging deformation treatment was performed.
[0064] The rods prepared in step S4 of Examples 1, 2, and Comparative Example 1 were characterized using a metallographic microscope, and the results are as follows: Figure 1 As shown, where Figure 1 In Figure a, the metallographic image of the rod prepared in step S4 of Comparative Example 1 shows that the rod does not contain TA1 reinforcement particles and the average grain size of the rod is 15 μm. Figure 1 Figure b is a metallographic image of the rod prepared in step S4 of Example 1. As can be seen from the figure, the TA1 reinforcement particles are uniformly dispersed inside the rod without obvious segregation. The average grain size of the rod is 12 μm. Figure 1 Figure c shows the metallographic image of the rod prepared in step S4 of Example 2. As can be seen from the figure, the TA1 reinforcement particles are uniformly dispersed within the rod, without significant segregation. The average grain size of the rod is 10 μm. This indicates that the TA1 reinforcement particles can improve the recrystallization degree of the matrix material and significantly refine the grain size during differential temperature extrusion of the composite material. Smaller grain sizes result in higher tensile strength. Furthermore, the absence of significant segregation of the TA1 reinforcement particles in the composite material ensures that the composite material is less prone to fracture due to localized stress overload during plastic deformation.
[0065] Figure 2 The images shown are EBSD images of the bars after rotary forging deformation treatment in step S5 of Example 1 and Comparative Example 1 at 500x magnification. Figure 2 In Figure a, the bar after rotary forging deformation treatment in step S5 of Example 1 is viewed at 500x magnification using the EBSD method. Figure 2 Figure b shows the EBSD image of the bar after rotary forging in step S5 of Comparative Example 1 at 500x magnification. Comparing the two figures, it can be seen that the bar obtained after rotary forging in Example 1 has denser small-angle grain boundaries inside the grains, and more fine deformed grains are broken up by deformation. This indicates that adding TA1 reinforcing particles in combination with the rotary forging process can enable the composite material to achieve a more severe degree of deformation.
[0066] Figure 3 The images shown are KAM images of the bars after rotary forging deformation treatment in step S5 of Example 1 and Comparative Example 1, magnified at 500x. Figure 3 In Figure a, the bar after rotary forging deformation treatment in step S5 of Example 1 is plotted at 500x KAM. Figure 3 Figure b shows the KAM image of the bar after rotary forging in step S5 of Comparative Example 1 at 500x magnification. Comparing the two figures, it can be seen that the bar obtained after rotary forging in Example 1 has a larger local crystallographic orientation deviation inside the grains, indicating a more severe deformation degree and more crystallographic defects such as geometrically necessary dislocations inside the grains, which can provide more nucleation sites for the next step of aging precipitation.
[0067] The grains with significant local orientation differences in the bar obtained by rotary forging in step S5 of Example 1 were further characterized using a transmission microscope. The results are as follows: Figure 4 As shown, by Figure 4 It can be seen that crystallographic defects such as nanocrystals and stacking faults exist in grain regions with large differences in crystal orientation, and nanoscale tensile twins also appear, indicating that a large number of defects that are conducive to the nucleation of precipitated phases are generated inside the material after rotary forging deformation.
[0068] The mechanical properties of the rare earth magnesium-based composite materials prepared in Examples 1-4 and Comparative Examples 1-2 were tested respectively, and the test results are shown in Table 1.
[0069] Table 1
[0070]
[0071] As shown in Table 1, the yield strength and tensile strength of the rare earth magnesium-based composite materials prepared in Examples 1-4 are higher than those prepared in Comparative Examples 1-2. This demonstrates that, compared to simply using metal particles combined with aging treatment to strengthen magnesium alloys, or simply using rotary forging combined with aging treatment, this invention, by combining TA1 titanium alloy spherical particles with rotary forging followed by aging treatment, can significantly improve the strength of the final rare earth magnesium-based composite material while also ensuring its plasticity.
[0072] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.
Claims
1. A method for preparing a high-strength rare-earth magnesium-based composite material, characterized in that, The preparation method is as follows: S1. By mass percentage: 3-10 wt.% of TA1 titanium alloy spherical powder, with the balance being Mg-Gd-Y-Zr alloy; S2, Manufacturing ingots; S3. Homogenize the ingots obtained in S2; S4. The ingots treated by S3 are extruded and deformed to obtain bars. S5. Perform rotary forging deformation on the bar obtained in S4, and reverse the feeding direction after each rotary forging process. S6. Aging treatment is then performed on the bars that have been treated in S5.
2. The preparation method as described in claim 1, wherein in step S2, the ingot is prepared using a semi-solid stirring casting process, specifically as follows: The Mg-Gd-Y-Zr alloy is melted at 720℃. After the alloy is completely melted, the furnace temperature is lowered to 625~640℃ and held for 5~10 minutes. When the melt is semi-solid, TA1 titanium alloy spherical powder is added. The mixture is stirred at 400~600 rpm for 30~40 minutes. The furnace temperature is then raised to 680~700℃ and stirred at 400~600 rpm for 20~30 minutes. The mixture is then cast into an ingot.
3. The preparation method according to claim 1, wherein in step S3, the homogenization treatment specifically involves: dissolving the ingot obtained in step S2 at 480~520℃ for 8~12 hours.
4. The preparation method according to claim 1, in step S4, the bar is prepared by differential temperature hot extrusion deformation process, specifically: the ingot after treatment in S3 is preheated to 450~500℃, the extrusion die is preheated to 400~450℃, and then forward extrusion is performed under the condition of extrusion ratio of 25:
1.
5. In the preparation method according to claim 1, in step S5, the rotary forging deformation treatment specifically involves controlling the deformation amount per pass to be 2%~10% and the total deformation amount to be 20%~45%.
6. The preparation method according to claim 1, wherein in step S6, the aging treatment specifically involves aging the bar material treated in S5 at 200°C for 40-50 hours.
7. The preparation method according to any one of claims 1-6, wherein in step S1, the average particle size of the TA1 titanium alloy spherical powder is 10 μm.
8. The preparation method according to any one of claims 1-6, wherein in step S1, the Mg-Gd-Y-Zr alloy comprises, by mass percentage, the following components: 8~10 wt.% Gd, 2~4 wt.% Y, 0.1~0.5 wt.% Zr, unavoidable impurities ≤0.25 wt.%, balance Mg.
9. A high-strength rare-earth magnesium-based composite material prepared by the method according to any one of claims 1-8.
Citation Information
Patent Citations
Preparation method of ultrahigh-strength low-rare-earth nano gradient magnesium alloy
CN108728713A
Micron titanium particle reinforced magnesium rare earth based composite material
CN114411031A
